THE EFFECTS OF THROWING PROGRAM TO MOTOR SKILLS DEVELOPMENT OF AUTISM CHILDREN - Phairot, Natnapa; Tengku Sulaiman, RajaSyed; Sriwisut, Panu (Academic Journal of Thailand National Sports University, 2022)
The purposes of this study were to study and compare the effect of training program upon motor skills of the children with autism between before and after training. The population used for this study included fourteen 6 – year - old students with autism at Special Education Center 4, Trang province. The research instrument is the pin throwing test. The content validity determined by the IOC (Index of item Objective Congruence) was rated at 0.86. The whole reliability of the test as shown by The Pearson Product Moment Correlation Coefficient was 0.77. Training period of 8 weeks consisted of 4 days per week (Monday, Tuesday, Wednesday, and Thursday respectively). Test of the motor skills of the autism children performed in the frist and the last week of training period. The statistics used for data analysis were mean, standard deviation, and t - test. The results of this study showed that the after training motor skills level of children with autism was statistically significantly (p < .05) higher than that before training.